Node retraction during patterning of the urinary collecting duct system. Issue 1 (8th October 2014) - Lindström, Nils O.; Chang, C.‐Hong; Valerius, M. Todd; Hohenstein, Peter; Davies, Jamie A.
Abstract This report presents a novel mechanism for remodelling a branched epithelial tree. The mouse renal collecting duct develops by growth and repeated branching of an initially unbranched ureteric bud: this mechanism initially produces an almost fractal form with young branches connected to the centre of the kidney via a sequence of nodes (branch points) distributed widely throughout the developing organ. The collecting ducts of a mature kidney have a different form: from the nephrons in the renal cortex, long, straight lengths of collecting duct run almost parallel to one another through the renal medulla, and open together to the renal pelvis. Here we present time‐lapse studies of E11.5 kidneys growing in culture: after about 5 days, the collecting duct trees show evidence of 'node retraction', in which the node of a 'Y'‐shaped branch moves downwards, shortening the stalk of the 'Y', lengthening its arms and narrowing their divergence angle so that the 'Y' becomes a 'V'. Computer simulation suggests that node retraction can transform a spread tree, like that of an early kidney, into one with long, almost‐parallel medullary rays similar to those seen in a mature real kidney.